Untersuchungen über Ablagerungen und Böden im eiszeitlichen Gletschergebiet Nodritaliens - Fränzle, Otto (ERDKUNDE, 1959)
In the first part of this paper the respective climax soils found on pleistocene deposits of clear stratigraphic position are described, and their applicability as index horizons is discussed. With the aid of the insights gained in the western and middle Po-Plain it is attempted to divide the Quaternary of the Garda region. The present results confirm Penck’s (1909) opinion and contradict that of Cozzaglio (1934) and Venzo (1957). The pedogenetic survey of a loess profile of the same region shows its early Wurm age; the soil developed from this loess belongs to a rather pronounced early Wurm interstadial. Finally the common character of the basal soliflual horizons is pointed out, and several examples of biphasic loess-sedimentation following this initial solifluction phase in the Wurm age are mentioned.